Sedimentation engineering - Vanoni, Vito A. (ASCE manuals and reports on engineering practice ;, 2006)
This classic reference provides an excellent text for understanding the nature and scope of sedimentation problems, methods for their investigation, and practical approaches to their solution. The book focuses on sediment control methods for watersheds, streams, canals, and reservoirs. Originally published in 1975, this is still considered the foremost text on sedimentation engineering. This classic edition, which includes a new index, will be beneficial to hydrologists, geomorphologists, sedimentologists, land-use planners, soil conservation specialists, and environmental, hydraulic, and agricultural engineers. Contents include: Nature of Sedimentation Problems; Sediment Transportation Mechanics; Sediment Measurement Techniques; Sediment Sources and Sediment Yields; Sediment Control Methods; Economic Aspects of Sedimentation; and American Sedimentation Law and Physical Processes. --